Investigating the Mediating Role of Loneliness and Attachment Styles in the Relationship between Internet Addiction and the Dark Tetrad Personality Traits - Atiyeh Haghi Khalifeh; Soheil Abousaedi Jirofti; Touraj Hashemi Nosrat Abad (مطالعات روانشناختی)
The present study was conducted with the aim of investigating the mediating role of loneliness and attachment styles in the relationship between internet addiction and the dark tetrad personality traits. The research was descriptive-correlational with path analysis. The statistical population of the research included the students of Tabriz University in the academic year 2023-2024, and by available sampling method, 395 people were selected. The research tools included dark tetrad personality traits, internet addiction, adult attachment style questionnaires and university of California Los Angeles loneliness scale. Path analysis method were used for data. The fit indices showed that the designed model has a good fit. The findings showed that there is a direct and significant relationship between dark personality traits and internet addiction. Also, the indirect effect of the dark traits of sadism and psychopathy through the feeling of loneliness and the indirect effect of Machiavellianism through insecure attachment anxiety on internet addiction was positive and significant. As a result, feelings of loneliness and attachment styles mediate the relationship between internet addiction and dark tetrad personality traits. The results of the present study can help therapists to design appropriate treatments and prevent internet addiction.